Microsoft Internet information services 7.0. (Solution accelerators., 2008)
This guide provides a consistent structure for addressing the decisions and activities critical to the successful implementation of the Microsoft® Internet Information Services (IIS) 7.0 infrastructure. Key issues, such as resource, application, and hosting requirements, are addressed, and the reader can determine the capacity needed from the proposed hosting infrastructure. This guide takes an application-centric approach to planning IIS: It focuses first and foremost on the applications to be hosted by IIS and their requirements; it then applies these applications to specific IIS instances. Finally, it scales the hardware appropriately for each IIS instance. Additional content focuses on the more organization-specific issues of planning points, workloads, architecture decisions, and choosing an edition of Windows Server® 2008 best suited to the business need.